Dal giornale al testo poetico ... (2001). The essays in Italian, with links to the essays in German (Studia theodisca, 2011)
Studia theodisca – Dal giornale al testo poetico. I «Berliner Abendblätter» di Heinrich von Kleist (2001). The essays in Italian, with links to the essays in German.